2014
DOI: 10.5812/ircmj.14463
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Testicular Damage in Busulfan Treated Mice

Abstract: Background:Advancement in the treatment of various types of cancer has led to greater patient survival. These treatments essentially have toxic effects on different kinds of cells, such as germ cells. Infertility as one of the side effects of cancer treatment has changed the quality of life of young cancer survivors dramatically. Melatonin is an antioxidant with receptors in the reproductive systems.Objectives:We supposed that melatonin, as an antioxidant, may protect testis against the toxic effects of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Then, we constructed the models of spermatogenic dysfunction by busulfan. Current studies have demonstrated that busulfan treatment can markedly cause the apoptosis of germ cells and impair normal spermatogenesis 232425. In this study, our results also showed that normal spermatogenesis was gradually impaired at 4 weeks after busulfan treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Then, we constructed the models of spermatogenic dysfunction by busulfan. Current studies have demonstrated that busulfan treatment can markedly cause the apoptosis of germ cells and impair normal spermatogenesis 232425. In this study, our results also showed that normal spermatogenesis was gradually impaired at 4 weeks after busulfan treatment.…”
Section: Discussionsupporting
confidence: 77%
“…They declared that although the mechanism is not clear, it acts probably by decreasing oxidative stresses. In another study, it was achieved the protective effect of melatonin in busulfan treated mice ( 28 ). Apparently, melatonin treatment produces antioxidant effect in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin co‐administration increased sperm count and motility and decreased rates of abnormal sperm. In addition, busulfan increased apoptosis in germ cells and seminiferous tubules . On the other hand, melatonin co‐administration either significantly or non‐significantly decreased apoptosis in seminiferous tubules and germ cells .…”
Section: Resultsmentioning
confidence: 93%
“…Busulfan (butane‐1,4‐diyl dimethanesulfonate) is an alkylating drug and used as an alleviating management in malignant diseases, including polycythemia vera and myeloproliferative disorders . Busulfan is a very toxic chemotherapy drug, which causes side effects in multiple organs, including the reproductive system . Busulfan induced disruption in seminiferous tubules structure, degeneration in germinal cells and a significant decrease in thickness of the seminiferous tubules in the testis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation